1982
DOI: 10.1159/000198694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Peptic Activity in the Rat Stomach

Abstract: The action of ethanol on peptic activity in the stomach was evaluated by studying ethanol-induced changes in pepsinogen secretion in the rat in vivo and the effects of ethanol on pepsinogen and pepsin in vitro. Irrigation of the stomach with 3% ethanol in 100 mM HCl plus 50 mM NaCl had no effect on pepsinogen secretion, whereas 10 and 20% ethanol gave maximal increases of about 40 and 65%, respectively. 10% ethanol in 150 mM NaCl (pH 5.0) stimulated pepsinogen secretion maximally by about 60%. 10% ethanol in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…As the gastric mucus glycoprotein of patients with ulcers is extensively degraded [6], it is possible that the beneficiary effect of ethanol on ulcer heal ing is a direct consequence of its inhibitory effect on peptic activity towards the mucus glycoprotein. It should be borne in mind, however, that in addition to this positive top ical effect, ethanol is known to diffuse rapidly across the gastric epithelium causing mor phological damage to the mucosa, and to affect the secretion of acid and pepsin [1,8,18]. Thus, the effect of ethanol on gastric mucosa is a complex one and appears to be multidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…As the gastric mucus glycoprotein of patients with ulcers is extensively degraded [6], it is possible that the beneficiary effect of ethanol on ulcer heal ing is a direct consequence of its inhibitory effect on peptic activity towards the mucus glycoprotein. It should be borne in mind, however, that in addition to this positive top ical effect, ethanol is known to diffuse rapidly across the gastric epithelium causing mor phological damage to the mucosa, and to affect the secretion of acid and pepsin [1,8,18]. Thus, the effect of ethanol on gastric mucosa is a complex one and appears to be multidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 10 and 20% ethanol appear to increase pepsinogen secretion in the rat, but to inhibit activation of pepsinogen to pepsin [22], Conversely peptic degradation of gastric mucus appears to be inhibited by ethanol both at low and high concentrations [23],…”
Section: ]mentioning
confidence: 99%
“…How ever, ethanol hyperosmolarity does not pro vide a satisfactory explanation for its nox ious effects on the mucosa. In fact inhibition of peptic activity by ethanol may occur, for instance, also below its isosmotic concentra tion to plasma [23], while hyperosmotic con centrations of alcohol exhibit effects that do not exactly duplicate those of equiosmolar agents [25], For example the stimulatory effect on pepsinogen secretion in rats is far more marked with other hyperosmolar solutions than with ethanol [22] and even the severity of mucosal damage is minor with ethanol than with equiosmolar solutions [25,26]. It has also been suggested that the actual os motic effect exerted by alcohol on the gastric mucosa may be less than that expected from its theoretical osmolarity [26].…”
Section: Osmotic Effectsmentioning
confidence: 99%
“…The selflimiting process ensures uniform coverage on the whole substrates and also on complex three-dimensional features. The technique is recognized for providing pinhole free films under suitable conditions [5].…”
mentioning
confidence: 99%